MEMAHAMI KARAKTERISTIK PERILAKU KONSUMEN PADA ERA SOCIETY 5.0 - Rodhiah, Rodhiah; Maitreyaty, Maitreyaty; Gracio, Steven; Tanuwijaya, Aurelius Yervant (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
The development of the society 5.0 era has shifted consumer purchasing behavior especially in generation z from traditional retail to electronic and online platforms enabled by advanced digital technology due to its speed, efficiency, and practicality. With this, to increase competitive advantage and increase sustainable consumer buying interest, marketers must react to changes in consumer behavior characteristics quickly. The activity partner is engaged in a culinary business located in Cipondoh-Tangerang. In their activities, partners face several problems, especially in terms of knowledge of consumer behavior characteristics in the era of society 5.0. The activity aims to assist partners in an effort to increase knowledge about consumer behavior characteristics that can increase consumer buying interest and competitive advantage. The method of activity is carried out by providing an understanding related to the understanding of consumer behavior, namely: Definition of Consumer Behavior, Purpose of Understanding Consumer Behavior Characteristics, Introduction to the era of society 5.0, Change of era society 5.0 which has an impact on Consumer Behavior, Characteristics of Consumer Behavior in this Era in Choosing Products to be consumed, Strategies for Understanding the Characteristics of Consumer Behavior in this era. Providing understanding is done online by visiting directly to the partner location. The results of the activity show that partners can increase sensitivity to the characteristics of consumer behavior and business sustainability in marketing products sold according to consumer characteristics correctly.